Hillforts. From Emergence to Present Day - Merkevičius, Algimantas (Archaeologia Lituana, 2018)
The 19th volume of Archaeologia Lituana is dedicated to the topic of hillforts as important monuments of cultural identity of the past and present.Eleven scientific articles were published in this volume, nine of which have been based on papers presented during the international scientific conference “Hillforts. From Emergence to the Present Day.” Another two articles were written by people who had not participated in this conference.The idea of the mentioned conference of its organizers arose after finding out information about the initiative of the Seimas on June 23, 2015, based on the Decree No. XII-1845, in which the year 2017 was declared as the Year of Hillforts. This important initiative of the Seimas served as an inspiration for organizing the international scientific conference in 2017 to discuss the important issues related to hillforts and their study.The three-day conference was held in Vilnius and Klaipėda. It was attended by archaeologists from nine countries, which presented 25 papers during the course of two days.The first day of the conference was organized in Seimas of the Republic of Lithuania. Algimantas Merkevičius, Chairman of the Organizing Committee, started the conference with a short welcome speech. The conference was welcomed and opened by members of the Seimas Prof. Eugenijus Jovaiša and Prof. Arūnas Gumuliauskas. In the next day of the Conference, on the 20th of October, a tour was organized for the participants of the conference that led them through the Vytautas Magnus War Museum and several hillforts and castles on the way from Kaunas to Klaipėda. On October 21, the third day of the conference was held at Klaipėda University.The articles published in this volume are grouped in a chronological order and cover a long period of time, from Prehistory to the late Medieval Period, starting with early hilltop settlement sites and the emergence of fortified settlements up to the construction of masonry castles on hills and other elevated locations across the landscape during the Middle Ages.This volume opens with an article by Estonian archaeologist, Professor of the University of Tartu Valter Lang, the guest lecturer of the conference. The first part of the article reviewed an investigation of early fortified settlements in the eastern Baltic Region and provided with the earlier interpretations of this type of settlement sites. In the second part of the article, Lang, relying on the material culture of the early fortified settlements and recent investigations on the ethnogenesis of the Baltic and Finnic people, has put forward a new hypothesis, claiming that the fortified settlements in the eastern Baltic Region could have been built by a new inhabitants that could have come from the eastern European forest belt.Two articles in this volume are devoted to the research of fortified and hilltop settlements in the Czech Re- public. They provided our readers with new information and insights on the appearance and the development of fortifications as well as the studies of hillforts in this part of Central Europe. The article by Josef Hložek, Petr Menšík, and Milan Procházka reviewed the emergence and development of hilltop and fortified settlements in southern Bohemia from the beginning of the Prehistoric Period to the end of the Middle Ages. The authors discussed the main features of fortified settlements, as well as the classification, chronology, functions, and de- velopment of fortifications over several millennia.In the next article, Roman Křivánek analyzed the use of geophysical methods for investigating Czech hillforts. The article discusses the development of geophysical research of fortified sites in the Czech Republic and the potential this non-destructive method has in studying the different types of settlement sites. This article also presents the results of this type of research in seven sites to illustrate the results, possibilities, and limitations of this method.The hillforts of Central Nadruvians, dated back to the 1st part of the 1st millennium AD, are focus of Russian archaeologists Olga Khomiakova, Ivan Skhodnov, and Sergey Chaukin. The authors touch upon many aspects of hillforts, such as their morphological characteristics, the distribution of these sites across the landscape, and their functions and significance for society. The main idea of their study is that these sites served as social centers in the discussed area. Some of the most important hillforts, located in the valleys of the Prieglius River and its tributaries, were described in further detail.Four articles in this volume are devoted to the analysis and interpretations of materials obtained during the investigations of late hillforts in various parts of Lithuania. In the first article, Ramūnas Šmigelskas, based on the results of his own small-scale archaeological excavations carried out in the Palace of the Vilnius Upper Cas- tle in 2016 and nine radiocarbon dates obtained during these investigations, aims to answer the question when a wooden castle was built on Gediminas Hill. Another important conclusion that he offered, which is based on radiocarbon data, is that the Gediminas Hill was settled during the 7th –5th century BC. The review of archaeo- logical excavations, which took part in this site throughout the whole of the 20th century, are also an important part of this study.The results of geophysical research, soil analysis, and archaeological small-scale excavations in the Senieji (Old) Trakai Castle and its settlement site were summarized in an article written by a group of seven researchers: Albinas Kuncevičius, Inga Merkytė, Justina Poškienė, Regina Prapiestienė, Rokas Vengalis, Gintautas Vėlius, Jonas Volungevičius. The article also reviews the written sources and historical studies as well as previous ar- chaeological excavations at the Senieji (Old) Trakai Castle. The main focus of this article is the transformation of the natural environment and landscape during the building activities of the castle.Mantas Užgalis analyzes in his article the hillforts of the Lamata land, which located in the southern part of western Lithuania. The author has counted 22 hillforts in the area under examination. Most attention is payed to the paleogeographical reconstruction of these fortified settlements, dated from second part of the 1st Millennium AD to the 13th century. The article also sets the political and administrative center of the Lamata land, which, according to Užgalis, was in the Skomantai Hillfort.In her article, Dovilė Baltramiejūnaitė reviewed the features and development of wheel-turned pottery dated to the 10th –14th centuries and found in the hillforts of the northeastern part of the area attributed to the Jotving- ian tribes. The morphological, technological, and decorative features of this pottery were examined. The stages of development, typology, chronology, classification, and contexts of wheel-tuned ceramics were discussed.The last article devoted to the topic of hillforts is produced by Ukrainian archaeologist Sergey Panishko on the “motte” type fortifications of the Medieval, so-called Lithuanian Period in the Volyn land. The author of- fered a classification of these late fortifications, presented their main characteristics, tried to trace the origin, and discussed their chronological development.Two articles in this volume are presented not by the participants of the mentioned conference and not devoted to the topic of hillforts. In the first of them, Erika Buitkutė and Giedrė Motuzaitė Matuzevičiūtė, using research methods for the investigation of ecofactual material, tried to determine the function of a wooden building dis- covered during the archaeological excavations in the eastern part of the Palace of the Lower Castle in Vilnius, which, according to the authors, could have served economic purposes.In the second catalog-type article, Russian archaeologists Vladimir Dryakhlov and Vladimir Kulakov published the data and the related interpretations on an items collection from the Merovingian epoch that is stored in the Alexander Pushkin State Art Museum (Moscow). According to the authors, these items, dated back to the 6th–7th centuries AD, were mainly found in the eastern territories of the Frankish tribes and belonged to the members of the Frankish aristocracy, who practiced their native, traditional religion.In the chapter “In memoriam” Prof. Mykolas Michelbertas briefly reviewed the scientific achievements of the famous Latvian archaeologist and historian Ēvalds Mugurēvičs, who passed away at the end of 2018. It is important to note that Mugurēvičs was an editorial member of the journal Lietuvos archeologija from 2000 to 2005, and in 2013, he was awarded to the Cross of the Knight of the Order for Merits to Lithuania.In the chapter “Publications of the Department of Archaeology,” Algimantas Merkevičius briefly presents a book published in 2018 that is devoted to the Early Metal Period settlement sites of Lithuania. The book contains basic data about more than 500 settlement sites of the period.In our usual chapter titled “Scientific Life Chronicle,” Violeta Vasiliauskienė overviews the key academic activities of the Archaeology Department’s teachers and students.We hope that this volume of Archaeologia Lituana will be interesting and useful to our readers.Algimantas Merkevičius
Keywords: none